FORMULATION AND EVALUATION OF MICROSPHERES CONTAINING IMATINIB MESYLATE USING SODIUM ALGINATE BY CHEMICAL CROSS LINKING METHOD - Periasamy, Senthil S; Sandu, Nagesh R; Loganathan, Senthilkumar K (Journal of Drug Delivery and Therapeutics, 2012)
The present research deals with formulation of microspheres containing an Anti-cancer drug Imatinib mesylate reduce the side effects and frequency of dosing. It is currently registered and used for two indications, Chronic Myeloid Leukemia (CML) and Gastrointestinal Stromal Tumors (GISTs). Imatinib mesylate loaded microspheres was formulated by using Sodium Alginate polymer by Chemical CrossLinking method to develop a sustained release dosage form. The effect of concentration of polymer ratio on the microspheres properties like percentage of drug loading, biodegradability, drug release kinetics, particle size, encapsulation efficiency, angle of repose, bulk density, SEM, DSC and XRD were investigated in our study. Moreover, the kinetics of Imatinib Meyslate released from different formulations of microspheres were analyzed using four different theoretical models, that is Zero order, First order, Peppa’s and Higuchi models. Microspheres prepared with Glutaraldehyde showed different release kinetics. Increasing the polymer concentration decreased the release rate of Imatinib Meyslate from microspheres because of formation of greater structural strength and more tightly texture with the drug. Besides, microspheres gave an adequate fit to either zero order or first order kinetic models, depending on the extent of cross linking reaction between drug and the cross linking agent. Key Words: Sodium Alginate, Imatinib Mesylate, microsphere, chemical cross linking, release kinetics.